A corpus-based study of the use of “BE” in Malay ESL learner essays / Roslina Abdul Aziz - Roslina, Abdul Aziz (2018)
This corpus-based study investigates (i) the distributional patterns for each form and function of BE in the Malay ESL learner essays, (ii) the patterns of grammatical and ungrammatical uses of BE by the learners and (iii) the extent of influence of the syntactic environments on the grammatical and ungrammatical uses of BE. The data for the study were harvested from the Malaysian Corpus of Learner English (MACLE). A total of 366 Malay learner essays were extracted from MACLE to form the Malay ESL learner sub-corpus. LOCNESS (Louvain Corpus of Native English Essays), which contains essays written by native speaker learners, was chosen to be the control corpus. In preparing the corpora for analysis, LOCNESS was tagged using CLAWS POS tagger, while MACLE was manually tagged using tagsets developed based on the analytical parameters set for this study. WordSmith Tools Version 5 was utilised to analyse the corpora. The study employed both quantitative and qualitative analyses. The quantitative analysis encompassed the frequency counts of all grammatical and ungrammatical uses of BE, while the qualitative analysis involved textual analysis on the grammatical and ungrammatical BE constructions. The quantitative findings reveal significantly higher grammatical use of BE in the Malay learner data, which is supported by the qualitative findings, which reveal the use of a wide range of forms and functions of the verb in predominantly more structurally complex constructions. In addition, the study has also unveiled the patterns of the most persistent ungrammatical use of BE namely, overgeneration and omission. Finally, based on the findings, the study proposes a corpus consultation model for the teaching of BE to ESL learners in Malaysian universities.